Ordered Mesoporous Electrodes for Sensing Applications - Scala Benuzzi, María Luz (2023)
Electrochemical sensors have become increasingly relevant in fields such as medicine, environmental monitoring, and industrial process control. Selectivity, specificity, sensitivity, signal reproducibility, and robustness are among the most important challenges for their development, especially when the target compound is present in low concentrations or in complex analytical matrices. In this context, electrode modification with Mesoporous Thin Films (MTFs) has aroused great interest in the past years. MTFs present high surface area, uniform pore distribution, and tunable pore size. Furthermore, they offer a wide variety of electrochemical signal modulation possibilities through molecular sieving, electrostatic or steric exclusion, and preconcentration effects which are due to mesopore confinement and surface functionalization. In order to fully exploit these advantages, it is central to develop reproducible routes for sensitive, selective, and robust MTF-modified electrodes. In addition, it is necessary to understand the complex mass and charge transport processes that take place through the film (particularly in the mesopores, pore surfaces, and interfaces) and on the electrode in order to design future intelligent and adaptive sensors. We present here an overview of MTFs applied to electrochemical sensing, in which we address their fabrication methods and the transport processes that are critical to the electrode response. We also summarize the current applications in biosensing and electroanalysis, as well as the challenges and opportunities brought by integrating MTF synthesis with electrode microfabrication, which is critical when moving from laboratory work to in situ sensing in the field of interest.